Hospital Dentistry: A multiprofessional view in a Public Institute of Amazonas (Research, Society and Development, 2022)
Some systemic diseases can be aggravated due to their correlation with oral health, demonstrating the importance of integrating the dentist in the multidisciplinary team in the hospital context. The present study aimed to know the view of the health professional, of this team, regarding the presence of the dentist in the hospital environment. Data were collected through a self-administered questionnaire with 131 health professionals who work at the Instituto de Saúde da Criança do Amazonas (ICAM). The results revealed that 74.80% (n=98) of the participants were female, with 75.57% (n=99) in the category of nursing technicians. The importance of the dentist's presence in the hospital multidisciplinary team was unanimous according to the participants. The nursing team is most responsible for the oral hygiene of patients in the absence of the dentist. In relation to the change noticed by the group in relation to the performance of the CD in the hospital, it was observed that 57.25% (n=75) of the research participants indicated an improvement in the oral health of hospitalized patients. It was concluded that the multidisciplinary hospital team believes in the insertion of the dentist in the hospital, as it can provide benefits in the integral care of the patient, reestablishing an improvement in the systemic and oral condition.